INDIVIDUAL CENTERED APPROACH IN SOCIAL WORK PRACTICE: CARL ROGERS AND ROGERIAN THERAPY (Third Sector Social Economic Review, 2022)
Social work, as an application-oriented profession based on social justice and on the basis of human rights, uses many theoretical approaches during professional intervention in order to offer a more effective treatment to the clients in solving their problems. These theoretical approaches, with an eclectic understanding from many different disciplines, provide practitioners with a general framework on how professional service delivery should be. One of the theoretical approaches used in social work practices is the “Person-Centered Approach” developed by Carl Rogers in the 1950s. While this approach argues that the only actor that affects the life of the individual is himself, it opposes the practices with a guiding attitude and puts people in the center. Empathy, acceptance, and respect are the three key components of this approach. In this study, it is aimed to understand what the person-centered approach is and how it can be used in social work intervention. In line with the aforementioned aim, the theoretical framework of the individual-centered approach is built in first part, the use of the individual-centered approach in social work practices, including case analysis, is discussed in the second part, and in the last part, the study is completed by making an evaluation. The concept of “client”, which is frequently mentioned throughout this study, is used alone in a way to meet other concepts that are referred to as “counselee”, “service recipient” and/or “care-reciever” in mental health terminology.
Keywords: Social Work; Person-Centered Approach; Therapy; Client; Carl Rogers